Exploring Stakeholder Activism in an Age of Social Media: A Case Study of Fashion Revolution Day and Corporate Responses. - Cox, Laurence (2014)
Social media is increasingly influencing the way corporations and societies interact on a range of issues. This has given rise to stakeholder activism online and corporations becoming more active online. This study explores how activism online is formed and the impact it has upon the corporations it seeks to pressure. This is looked at through a case study of Fashion Revolution Day, which is a campaign calling for improvements to fashion supply chains as a result of disasters such as the Rana Plaza factory collapse in Bangladesh in April 2013. The corporate response is also examined with the focus on high-street fashion retailer Primark. Thematic coding forms the analysis, which is carried out on Twitter data from the campaign and the response to it is explored across Twitter, Facebook and the old media. The data suggested that Fashion Revolution Day achieved the necessary scale of response making it a successful first year for the campaign. However, any industry changes will take time and this will be the test for the campaign going forward. Actor self-interest was identified as a key motivation for those leading the campaign and the corporations being pressured. Primark’s use of social media has allowed it to be very flexible in response to crisis events. This indicates that while social media does shift the power relations between corporations and society, if it is fully embraced corporations can use it to their advantage.